INSIDENSI PENYAKIT BUSUK HITAM PADA TANAMAN BROKOLI (Brassica oleracea var. Italica) DI TOMOHON - Fei Sie Lumoly; Emmy Senewe; Guntur S.J. Manengkey (Universitas Sam Ratulangi, 2016)
ABSTRACKThis study aims to determine the symptoms, and incidence of black rot in broccoli. This research was conducted at multiple centers Tomohon on planting broccoli, namely in the Village Kakaskasen, Village and Village Kinilow Paslaten. The study lasted for 3 months that is April to June 2016. The research method was conducted in two places, namely the laboratory of Microbiology and Plant Pathology, Faculty of Agriculture Unsrat Manado and in the location of planting broccoli. This study uses a survey in the field with a purposive sampling and the object of research is the broccoli plants owned by farmers. Observations were carried out six times at intervals of one week. The first observation to a third observation is the observation of the broccoli plant vegetative phase, and the fourth to sixth observation is the observation of the broccoli plant generative phase. The results of this study show early symptoms of infectious disease-causing black rot in broccoli in the vegetative phase is there are yellow spots shaped like the letter V on leaves of broccoli, the area spotting eventually dries and turns brown and then fall, patches can then be spread to all leaves and plants. In the generative phase are rotten and black color on the mass of broccoli flowers. The incidence of infection causes black rot disease in plants of broccoli in the field showed differences in incidence of the disease in each sample location. The average incidence of black rot disease infection highest in the vegetative phase is in the Village Kakaskasen is 67.0% and the lowest incidence is in the Village Kinilow namely 28.7%, while on the generative phase is Village Kakaskasen highest incidence is 44% and the lowest incidence is Kinilow Village of 16.3%